Bridging India’s ethnobotanical traditions and Ayurveda: Exploring galactagogue plants in livestock and human care - Gajarmal, Amit; Baheti, Sandip; Patekar, Rashmi; Mane, Santosh; Sagar, Rashmi; S, Mahesh; Rath, Sudipta Kumar (Ethnobotany Research and Applications, 2025)
Background: Livestock are vital to rural and agrarian economies, yet enhancing lactation remains a persistent challenge. Ethnobotanical and ethnoveterinary galactagogue plants, deeply rooted in indigenous knowledge systems, offer a sustainable alternative to synthetic lactation stimulants. Drawing upon ancient literature of Ayurveda and traditional ethnoveterinary practices, plant-based remedies have long been used to improve milk production, aligning with modern goals of sustainable livestock management. Methods: This review systematically examined traditional and contemporary literature on ethnobotanical and ethnoveterinary galactagogues, sourcing data from Ayurveda ancient classic texts, ethnoveterinary documentation, and modern scientific studies. Plant species traditionally used to stimulate lactation were identified and categorized based on plant family, utilized parts and known phytochemical constituents. Results: The analysis identified over 170 plant species, predominantly from the Fabaceae family, with seeds and leaves being the most utilized parts in Indian traditional system of medicine. Key bioactive phytochemicals—including flavonoids, terpenoids, alkaloids, and phenolic compounds—were found to play potential roles in enhancing lactation. Pharmacological evidence suggests that these compounds may influence hormonal pathways associated with milk production. However, there remains a lack of standardized herbal formulations and clinical trials validating their efficacy and safety across diverse livestock species. Conclusion: Ethnobotanical and ethnoveterinary galactagogue plants represent a promising avenue for sustainable dairy management by bridging traditional wisdom with modern veterinary science. Future research should prioritize the standardization of herbal formulations, conduct rigorous clinical validation, and explore policy integration of plant-based galactagogues in veterinary & human healthcare. Promoting these plant-based solutions can reduce reliance on synthetic drugs while ensuring animal health, welfare, and productivity. Keywords: Ayurveda, Ethnoveterinary Medicine, Galactagogue Plants, Phytochemicals, Sustainable Livestock Management